Lifelong learning as a major trend in personnel training: theoretical and practical aspects - Olga Yu. Kalmykova; Natalia V. Ryumina; Svetlana N. Parfenova; Natalya V. Sukhankina (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The problem of forming conflictological competences of pedagogical staff in educational organization, which is associated with the increasing stressfulness of the organizational environment and multifunctional activities of teaching staff, is presented in the paper. The analysis of conflictological competences, which need to be formed within the framework of continuous conflictological education of university teachers, is given. The paper analyzes the methods and content of the module Conflict and Stress Management in the Educational Process of the retraining program Teacher of Higher Education. The aim of the research is to develop methodological recommendations aimed at improving the level of conflictological and stress-competence of teachers of Samara State Technical University, involving the use of modern educational technologies. This objective is achieved by means of the following tasks: conducting expert surveys (respondents: teachers and students of the university) in order to determine methods and techniques for improving conflictological and stress competence of teachers; creating training and methodological materials for students of professional development program Education Process Management: Psychological and Pedagogical Competence of a Technical University Teacher and retraining program Teacher of Higher Education in Samara State Technical University. Team-building for the students and teachers of the university. The study was conducted in several stages. Objectives of the theoretical stage of the research: to substantiate the significance of increasing the level of conflictological and stress competences of university teachers. Objectives of the diagnostic stage of the research: to monitor the level of professional stress of teachers; to conduct an expert survey to assess the significance of increasing the level of conflictological and stress-competences of university teachers. The respondents of the expert survey were the trainees of the professional development program Management of Educational Process: Psychological and Pedagogical Competence of a Technical University Teacher and the retraining program Teacher of Higher Education of Samara State Technical University. The following methods were used in the research: expert survey, observation, questionnaires, methods of quantitative and qualitative analysis of the results obtained. The experience of teaching the discipline Conflict and Stress Management in the Educational Process as part of the retraining programme Teacher of Higher Education of Samara State Technical University is presented. The prospective of the study is the further improvement of teaching methods to develop conflictological and stress-competence of teachers.